A Descriptive Qualitative Study of Consumer Satisfaction and Purchase Interest Among Shopee Users: Evidence from Bangun Purba District - Erik Estrada (International Journal of Economic and Tourism Research, 2026)
This study aims to provide an in-depth analysis of consumer satisfaction and purchase interest among Shopee users in Bangun Purba District. It explores how digital marketing strategies, service quality, and platform features influence consumer behavior in a localized context. A qualitative descriptive approach was employed to capture the subjective experiences of consumers. Data were gathered through in-depth interviews and participant observations with Shopee users from diverse demographic backgrounds. The analysis utilized Stuart Hall’s Reception Theory to categorize consumer interpretations and thematic analysis to identify key drivers of satisfaction and purchase intention. The results indicate that consumer satisfaction in Bangun Purba District is driven by interactive platform design, real-time engagement through features like Shopee Live, and effective promotional strategies. While the majority of users exhibit a Dominant-Hegemonic reading—readily accepting marketing messages due to informative interfaces—variations in education and experience lead to Negotiated and Oppositional stances. Furthermore, live streaming and video marketing significantly trigger impulsive buying behavior by creating a sense of urgency and exclusivity. This study is limited to a specific geographic area (Bangun Purba District). Theoretically, it enriches the literature on e-commerce by demonstrating how localized socio-cultural factors mediate digital reception. Practically, it suggests that e-commerce platforms and MSMEs must prioritize "visual trust" and culturally resonant communication over price-centric strategies. This research fills an empirical gap by providing a localized qualitative perspective on e-commerce satisfaction in a rural-urban transition area, offering nuanced insights that quantitative metrics often overlook.